1997
DOI: 10.1086/513633
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Procalcitonin Levels in Children with Bacterial or Viral Meningitis

Abstract: We measured the plasma procalcitonin levels in 59 children who were admitted to the hospital because of bacterial or viral meningitis. Eighteen children with acute bacterial meningitis had elevated procalcitonin levels (mean level, 54.5 micrograms/L; range, 4.8-110 micrograms/L). The procalcitonin levels in 41 children with viral meningitis were low (mean level, 0.32 micrograms/L; range, 0-1.7 micrograms/L; P < .0001). Assay of cerebrospinal fluid (CSF) cells and proteins and serum C-reactive protein showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
129
3
19

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(158 citation statements)
references
References 6 publications
7
129
3
19
Order By: Relevance
“…Others have found sensitivity and specificity values for procalcitonin in similar ranges (Table 3) [2,5,11,14,21,26,29,30,33]. However, the results reported by Worthington et al were quite different: serum procalcitonin did not help distinguish between infectious and noninfectious causes of prosthetic hip loosening [41].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Others have found sensitivity and specificity values for procalcitonin in similar ranges (Table 3) [2,5,11,14,21,26,29,30,33]. However, the results reported by Worthington et al were quite different: serum procalcitonin did not help distinguish between infectious and noninfectious causes of prosthetic hip loosening [41].…”
Section: Discussionmentioning
confidence: 91%
“…Numerous studies have shown procalcitonin is elevated in cases of bacterial infection or sepsis and levels are considerably higher in bacterial infections than in viral infections [2,5,11,14,21,26,29,30,33]. Procalcitonin increases 2 to 4 hours after the onset of sepsis, which is later than proinflammatory cytokines, such as interleukin 6 (IL-6), but considerably earlier than CRP [31].…”
Section: Introductionmentioning
confidence: 99%
“…PCT has been proven to be valuable in differentiating between bacterial and viral meningitis when determined in serum (Dubos et al., 2008; Gendrel et al., 1997; Viallon et al., 2011). However, the usefulness of PCT in serum of patients with bacterial meningitis after neurosurgical intervention is limited (Choi & Choi, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several studies have focused on the use of CRP in bacterial and viral respiratory infections in children, but the results have been inconsistent [6±8]. Therefore, most children with pneumonia are treated with antibiotics without knowledge of the causative agent.Procalcitonin (PCT) is a newly recognized marker of bacterial infection [9], it contributes to the differentiation between septic and other infections in neonates [10] and older paediatric patients [11]. In a panel of children in which the aetiology of infection was assessed [12], it was examined whether PCT can be applied for the discrimination between bacterial and especially pneumococcal pneumonia and viral aetiology of pneumonia.…”
mentioning
confidence: 99%